2020
DOI: 10.1042/bcj20190536
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β chaperone — lipocalin-type prostaglandin D synthase acts as a peroxidase in the presence of heme

Abstract: The extracellular transporter, lipocalin-type prostaglandin D synthase (L-PGDS) binds to heme and heme metabolites with high affinity. It has been reported that L-PGDS protects neuronal cells against apoptosis induced by exposure to hydrogen peroxide. Our study demonstrates that when human WT L-PGDS is in complex with heme, it exhibits a strong peroxidase activity thus behaving as a pseudo-peroxidase. Electron paramagnetic resonance studies confirm that heme in the L-PGDS–heme complex is hexacoordinated with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
(172 reference statements)
1
5
0
Order By: Relevance
“…Interaction between L-PGDS and G623R fibril. A remarkable feature of L-PGDS is its ability to coordinate two iron heme molecules with picomolar affinity while retaining its Aβ chaperone function 36 . Since the L-PGDS molecule is too small to be directly imaged in cryo-EM, here we utilized the L-PGDS-heme complex to visualize the binding locations of L-PGDS on the G623R fibril using bound heme as a contrast enhancer.…”
Section: Resultsmentioning
confidence: 99%
“…Interaction between L-PGDS and G623R fibril. A remarkable feature of L-PGDS is its ability to coordinate two iron heme molecules with picomolar affinity while retaining its Aβ chaperone function 36 . Since the L-PGDS molecule is too small to be directly imaged in cryo-EM, here we utilized the L-PGDS-heme complex to visualize the binding locations of L-PGDS on the G623R fibril using bound heme as a contrast enhancer.…”
Section: Resultsmentioning
confidence: 99%
“…The monomeric Ab peptides also bind at the entrance of the L-PGDS calyx with nanomolar affinity (Kanekiyo et al, 2007;Kannaian et al, 2019). We showed that L-PGDS might exert strong peroxidase activity when the first lipophilic ligand is iron-heme and that the produced reactive oxygen species might be contained within the enzyme by oxidizing the second ligand more peripherally or transiently bound to L-PGDS (Phillips et al, 2020). We posit that the strong ligand-binding ability of L-PGDS might facilitate the accumulation of AC drug molecules inside the calyx, their chemical modification (oxidation) and potentially interfere with the homeostasis of Ab peptides associated with AD.…”
Section: Introductionmentioning
confidence: 93%
“…Our tryptophan quenching analysis and ITC results established the direct interaction between CPM and TRD with L-PGDS ( Table 3). We have previously shown that human L-PGDS can interact with monomeric Ab(1-40) peptide and prevent its aggregation (Kannaian et al, 2019;Phillips et al, 2020). Thus, to determine if the binding of the AC drug molecules affects the L-PGDS chaperone function we used the Thioflavin T (ThT) fluorescence assay to monitor the spontaneous aggregation of Ab(1-40) peptide in the presence of L-PGDS/CPM and L-PGDS/TRD complex.…”
Section: Cpm Binds To L-pgds and Inhibits Its Chaperone And Disaggregmentioning
confidence: 99%
“…L-PGDS also binds heme itself, as examined by NMR (Phillips et al, 2020). The heme-binding L-PGDS is associated with the pseudo-peroxidase activity, which is proposed to contribute to the anti-apoptotic activity of L-PGDS against the H 2 O 2 -induced cytotoxicity (Phillips et al, 2020).…”
Section: Binding Of Heme-degradation Products and Hemementioning
confidence: 99%
“…X-ray crystallographic structures of human L-PGDS was also reported, in which fatty acids (Zhou et al, 2010) and polyethylene glycol used as precipitants (Perduca et al, 2014) are identified to be inserted into the central cavity of the molecule. The NMR structures of L-PGDS complexed with an L-PGDS-selective inhibitor AT56 (Irikura et al, 2009) or a variety of lipophilic (Qin et al, 2015) or hydrophobic (Shimamoto et al, 2007;Sreenivasulu et al, 2013;Inui et al, 2014;Kannaian et al, 2019;Low et al, 2020;Phillips et al, 2020) ligands were also already reported (Supplementary Table 4). Those structural information is useful for designing inhibitors specific for L-PGDS.…”
Section: Structural Characterization Of Lipocalin-type Prostaglandin D 2 Synthase By Nuclear Magnetic Resonance and X-ray Crystallographymentioning
confidence: 99%